STA-A3 Bypass Using Radial Artery Graft for Progressive Cerebral Infarction of Bilateral ACA Region after STA-MCA Bypass Surgery for Moyamoya Disease - Hirano, Yudai; Ono, Hideaki; Inoue, Tomohiro; Ohara, Kenta; Tanishima, Takeo; Tamura, Akira; Saito, Isamu (Asian Journal of Neurosurgery, 2022)
Direct revascularization surgery, such as superficial temporal artery (STA)-middle cerebral artery (MCA) bypass, is effective in preventing ischemia and hemorrhage for moyamoya disease. On the other hand, when ischemia of the anterior cerebral artery (ACA) region progresses after ipsilateral STA-MCA bypass, it is difficult to perform revascularization from the viewpoint of the donor artery. A 55-year-old woman with right hemiparesis was diagnosed with cerebral infarction due to moyamoya disease. Left STA-MCA bypass was performed with no postoperative complications, but memory impairment and decreased motivation were observed 2 months after the operation. Magnetic resonance imaging and angiography revealed new infarction in the bilateral ACA area and deterioration in the signal intensity of bilateral ACAs. Revascularization of the bilateral ACA regions was considered necessary, but the left STA was already used in the previous surgery. Therefore, STA-radial artery (RA)-A3 bypass using RA graft combined with right STA-MCA bypass was performed. STA-A3 bypass using an RA graft may be the optimal treatment for ischemia of the ACA region that progresses after STA-MCA bypass.
Keywords: moyamoya disease; anterior cerebral artery; bypass surgery; radial artery